2017
DOI: 10.1002/tea.21435
|View full text |Cite
|
Sign up to set email alerts
|

Misconception of sound and conceptual change: A cross‐sectional study on students' materialistic thinking of sound

Abstract: There is a concern that materialistic thinking—meaning the tendency to attribute a set of matter‐like properties to nonmatter concepts—is one of the central barriers that students face in the journey toward understanding scientific concepts. The cross‐sectional study presented here used the Sound Concept Inventory Instrument (SCII) (Eshach, [], Physical Review Physics Education Research, 10, 010202) to examine how Taiwanese students (N = 717: Grade 7 to undergraduate level) associate the nonmaterial concept of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 50 publications
0
26
0
5
Order By: Relevance
“…To cope with the limitations of multiple-choice tests, a multiple-tiers test was developed in various recent studies. Energy and momentums (Dalaklioğlu & Sekercioğlu, 2015) Fluid static (Kusairi et al, 2017) Impulse and momentums (Soeharto, 2016;Samsudin et al, 2015) Temperature and heat (Madu & Orji, 2015;Asri et al, 2017) Sport physics (Kartiko, 2018) Energy and force (Nwafor et al, 2015) Newtons' Law (Ergin, 2016) Electric circuits (Sadler & Sonnert, 2016) Gases (Çetin et al, 2009) Physical concept (Wind & Gale,2015) Heat transfer (Wibowo et al, 2016) Thermal physics (Malik et al, 2019) Moon phase (Saenpuk & Ruangsuwan, 2019) Energy material (Wijayanti et al, 2018) Light (Wartono & Putirulan, 2018) Heat concept (Haryono, 2018) Solid matter and pressure liquid substances (Handhika et al, 2018) Sound (Eshach et al, 2018) Hydrostatic pressure and Archimedes law (Berek et al, 2016) Chemistry Municipal chemistry (Milenković et al, 2016b) Chemical bonding (Vrabec & Proksǎ, 2016;Enawaty & Sartika, 2015) Enzyme Interacts (Linenberger & Bretz, 2015) Chemical bonding and spontaneity (Ikenna, 2015) Electrochemistry (Önder, 2017) Acid-base (Sadhu et al, 2017;Sadhu, 2019) Acid-base and solubility equilibrium. (Masykuri & Rahardjo, 2018) Biology Photosynthesis (Orbanić et al, 2016) Evolution of biology (Putri et al, 2017;Helmi et al, 2019) Natural science (Subayani, 2016;Murti & Aminah, 2019) Global warming (Fajarini et al, 2018) Ecology…”
Section: Simple Multiple-choice Testmentioning
confidence: 99%
See 1 more Smart Citation
“…To cope with the limitations of multiple-choice tests, a multiple-tiers test was developed in various recent studies. Energy and momentums (Dalaklioğlu & Sekercioğlu, 2015) Fluid static (Kusairi et al, 2017) Impulse and momentums (Soeharto, 2016;Samsudin et al, 2015) Temperature and heat (Madu & Orji, 2015;Asri et al, 2017) Sport physics (Kartiko, 2018) Energy and force (Nwafor et al, 2015) Newtons' Law (Ergin, 2016) Electric circuits (Sadler & Sonnert, 2016) Gases (Çetin et al, 2009) Physical concept (Wind & Gale,2015) Heat transfer (Wibowo et al, 2016) Thermal physics (Malik et al, 2019) Moon phase (Saenpuk & Ruangsuwan, 2019) Energy material (Wijayanti et al, 2018) Light (Wartono & Putirulan, 2018) Heat concept (Haryono, 2018) Solid matter and pressure liquid substances (Handhika et al, 2018) Sound (Eshach et al, 2018) Hydrostatic pressure and Archimedes law (Berek et al, 2016) Chemistry Municipal chemistry (Milenković et al, 2016b) Chemical bonding (Vrabec & Proksǎ, 2016;Enawaty & Sartika, 2015) Enzyme Interacts (Linenberger & Bretz, 2015) Chemical bonding and spontaneity (Ikenna, 2015) Electrochemistry (Önder, 2017) Acid-base (Sadhu et al, 2017;Sadhu, 2019) Acid-base and solubility equilibrium. (Masykuri & Rahardjo, 2018) Biology Photosynthesis (Orbanić et al, 2016) Evolution of biology (Putri et al, 2017;Helmi et al, 2019) Natural science (Subayani, 2016;Murti & Aminah, 2019) Global warming (Fajarini et al, 2018) Ecology…”
Section: Simple Multiple-choice Testmentioning
confidence: 99%
“…Because of that matter, some researches had been held to provide information about student understanding, especially in learning science concepts. The different insight of student concepts had been defined by a number of terms like "alternative conceptions" (Wandersee et al, 1994), "conceptual difficulties" (Stefanidou et al, 2019), "misconceptions " (Eshach et al, 2018), "mental models" (Wuellner et al, 2017), and others.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, even if students start viewing a certain phenomenon as a process, it is the wrong process mechanism that they have in mind. For instance, in a series of studies on sound [6,21,22], Eshach showed that students attribute materialistic characteristics to sound, and even if they view sound as a process of propagation from one place to another, they still view this process as a direct one (e.g., as a kind of substance that is being pushed and moved from a sound source to a listener). They do not see sound as an emergent process resulting from random collisions between a medium's particles.…”
Section: The Ontological Shift Approachmentioning
confidence: 99%
“…Indeed, many researchers show that learners "…face obstacles in mapping abstract, theoretical understanding of thermodynamic principles" [26] (p. 704). One of the barriers students may face stem from their materialistic thinking, which is defined by Eshach et al [22] as their tendency to associate materialistic properties to scientific concepts. Indeed, Reiner et al [12] and Chi [1,3] argue that naïve students tend to assign heat to the entities category, and thus explain phenomena related to heat in terms of matter and the characteristics they attribute to matter.…”
Section: Pedagogical Example Of Teaching About the Heat Transfer Pmentioning
confidence: 99%
“…There are multifaceted reasons behind this phenomenon, and one of which is the difficulty of forming a conceptual change from learners' prior understanding. Similar to learning scientific concepts such as sound, pressure, balance and so on (Eshach, Lin, & Tsai, 2018;Ozkan & Selcuk, 2016), learners need to move from an everyday concept to a scientific one. In many cases, the intended conceptual change happens, but others form a misconception (alternative concept), and some maintain their intact preconception.…”
Section: Concept Formation Of Scientific Modelsmentioning
confidence: 99%